Impact of Other Linguistic Behaviors on Urdu Language and Literature - Sadiq, Shakeel Amjad (sourcecoder, 2024)
Linguistic repository in the shape of words constitutes the body of a particular language. Language will be established and comprehensive provided its words are more and more tangible cum eloquent. In the context of a language, words carry the same importance as currency has for economic stability. An all-encompassing and collective society gives rise to a number of languages which affect each other. Resultantly, change appears within the meaning of words and their narration, culminating into an established language. Urdu language keeps within its fold amalgam of various languages and dialects. Urdu owed its origin to the interaction of Persian, Arabic and other regional languages. This praiseworthy language is more influenced by Persian, Punjabi and Sanskrit languages. Urdu adopted Persian and Arabic style of writing and alphabets. It has many original words of Arabic and Persian which have made their way into Urdu through various means. For that purpose, certain rules have been framed which shed detailed and comprehensive light upon linguistic effects of Persian upon Urdu.